AKTIVITAS MEDIA RELATIONS DINAS PARIWISATA EKONOMI KREATIF PEMUDA DAN OLAHRAGA KABUPATEN PESISIR SELATAN SUMATERA BARAT DALAM PUBLIKASI OBJEK WISATA PANTAI CAROCOK - Niko Pratama; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Carocok beach is one of the attractions that esotis for a vacation, with the gazebo place to relax, the beauty of a floating bridge over the sea, as well as water games banana boat, jet ski and boat donut that could spur travelers aderanalin. Carocok beach is managed by the Department of Tourism and Creative Economy Youth Sports South Coastal District of West Sumatra and strive to in the publication through the mass media. therefore, media relations is needed to facilitate a good relationship. The purpose of this study was to determine the form of media relations activities Creative Economy Tourism Department of Youth and Sports South Coastal District of West Sumatra in the publication attraction Carocok Beach, to determine the form of media relations with the Department of Tourism and Creative Economy Youth Sports South Coastal District of West Sumatra in the publication object Carocok beach tourism, and to determine the factors supporting the publication media relations attractions Carocok Beach. This study used descriptive qualitative method. Data collection techniques used are based on reality in the field through observation, interviews, and documentation. Informants in this study amounted to 17 people based on purposive. Data analysis techniques were used that model of interactive data analysis. As for checking the validity of the data the researchers used a technique participation and also the extension of triangulation. The results showed that the shape of activities media relations of the Department of Tourism and Creative Economy Youth Sports South Coastal District of West Sumatra in the publication attraction Carocok Beach pretty good. Which can be seen from the increasing number of visitors each year. As for the activity of its media relations in the form, press releases, events, press conferences and press tour. As for the media in publications such as news, local print media is the daily newspaper Metro Pos Padang, Padang Ekspres, People's Weekly Hope there are also electronic medi a such as television are TransTV, TVRI and the Internet. whereas the promotion through: billboards, brochures, exhibitions, and websites. Like wise form of media relations with the Department of Tourism and Creative Economy Youth Sports South Coastal District of West Sumatra in the publication type Beaches Carocok good enough. And shape its relationship through personal contact, information services and news, Anticipating the possibility of an emergency. Supporting factor is the openness of the media, cooperation and good relations, as well as technological advances. Keywords: Activitiesmedia relations, Publication,Carocok Beach.